Juan de Torquemada v polemice s husitským pojetím eucharistie - Ondřej Matys (Theatrum Historiae)
Thesis deals with Dominican theologian Juan de Torquemada and his approach to the Hussitism, the Utrakvist concept of the Eucharist in particular. Based on analysis of two polemical treatises of Torquemada, thesis focuses on strategy of argumentation and its instruments. On this basis thesis analyses particular textual topics related with concern of Eucharist theology. Further consideration mentions the inspirational influences projected in polemical writing of Torquemada. As a result of textual analysis focused on mentioned aspects, conclusion of this study identifies partly mainstream, but partly specific approach to the Utrakvist controversy.